2022
DOI: 10.3390/ijms23095186
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Exogenous Proline to Abiotic Stresses Tolerance in Plants: A Review

Abstract: Abiotic stresses are the major environmental factors that play a significant role in decreasing plant yield and production potential by influencing physiological, biochemical, and molecular processes. Abiotic stresses and global population growth have prompted scientists to use beneficial strategies to ensure food security. The use of organic compounds to improve tolerance to abiotic stresses has been considered for many years. For example, the application of potential external osmotic protective compounds suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 114 publications
5
85
0
1
Order By: Relevance
“…Among amino acids, the role of proline in stress acclimation has been widely studied and described. It may also serve as osmoprotectant and signalling molecule inducing other protective mechanisms under various abiotic stress conditions [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among amino acids, the role of proline in stress acclimation has been widely studied and described. It may also serve as osmoprotectant and signalling molecule inducing other protective mechanisms under various abiotic stress conditions [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, ROS scavenging in transgenic plants might correlate with MsTHI1 upregulation, which triggered the thiamine metabolism and the aggregation of chlorophyll to decrease the amount of ROS. The soluble protein and free Pro are key osmotic regulators, which can raise the osmotic potential of cells and boost plant tolerance to stressful conditions (Hosseinifard et al, 2022 ). In the present research, the soluble protein level in transgenic alfalfa was mainly greater than that in WT alfalfa during control or drought settings.…”
Section: Discussionmentioning
confidence: 99%
“…Under stress conditions, there is a decrease in the reserves of proline used by the plant to neutralize ROS. It is believed that proline’s protective effect is related to its ability to detoxify ROS [ 10 ], inhibit lipid peroxidation [ 41 ], and act as an osmoprotectant in the case of metal toxicity [ 42 ]. Several studies have shown that exposure to metals in micro-and nano-form has revealed changes in proline content in various plant species [ 24 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since both δ-ALA and proline are synthesized from a common precursor, glutamic acid, their role as antistressors can be interchangeable in vegetation periods and various plant conditions such as salinity, drought, and oxidative stress [ 2 , 42 , 46 ]. The present study showed an increase in δ-ALA, possibly due to barley’s enzymatic changes and ROS production.…”
Section: Discussionmentioning
confidence: 99%